ANALISIS KELELAHAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN WELDING DI PT MCDERMOTT BATAM - Taufik, Sulamat; Zetli, Sri (LPPM Universitas Putera Batam, 2023)
In Employees who perform welding are often exposed to heat sources, including sunlight and heat from welding machines because some employees perform welding outdoors. Cutting iron, heating, grinding, joining, painting and sanding are steps in the welding process that are performed in a work environment exposed to sunlight. Thus, the question of whether fatigue has an impact on employee performance at PT Mcdermott Batam must be answered. A person's fatigue level can be assessed by several methods, including subjectively using the Industrial Fatigue Research Committee (IFRC) questionnaire. The level of fatigue is assessed using this questionnaire. At PT Mcdermott Batam, employee performance is assessed using a questionnaire which is prepared based on employee performance criteria. The objectives of this study are to determine the level of employee fatigue using the IFRC method, to determine the level of employee performance in the welding section and to determine the level of relationship between fatigue and employee performance. This study uses simple linear regression test. The results showed that there is an influence between job fatigue on employee performance.